Electromyographic analysis of the arm muscles in front support exercises - Dias, Gladys Alexandra R. [UNESP]; Filho, J. Guazzelli [UNESP]; Rodrigues, J. A. [UNESP]; Gonçalves, M. [UNESP]; Büll, M. L. [UNESP] (My University, 2003)
The electromyographic activity of the biceps brachii - BB (long head), triceps brachii - TB (long head) and deltoideus - DA (clavicular portion) muscles, during the going (G) and return (R) phases in front support exercise, as well the efficacy of this exercise for the development of these muscles strength were studied in 10 male volunteers. The values were normalized through maximum voluntary isometric contraction (MVIC = 100%) and statistically analyzed using the Friedman, DMS and Wilcoxon non-parametric test. A value of p≤0.05 indicated significance (Campos, 1983). All the muscles presented higher electromyographic activity in the return phase of the movement. The triceps brachii was the muscle which had higher activity in both phases of the movement. It was concluded that the front support exercise is efficient for strength development mainly in the triceps brachii muscle.
Keywords: Biceps brachii; Deltoideus; Electromyography; Exercises; Triceps brachii; adolescent; adult; arm exercise; biceps brachii muscle; calculation; controlled study; deltoid muscle; electromyography; Friedman test; human; human experiment; male; movement (physiology); muscle isometric contraction; muscle strength; nonparametric test; normal human; statistical analysis; statistical significance; triceps brachii muscle; volunteer; Adolescent; Adult; Arm; Exercise; Humans; Male; Muscle Contraction; Muscle, Skeletal; Reference Values; Weight-Bearing